Factors associated with the incidence of obesity among civil servants in Sleman Regency - Renyaan, Erna Yati; Prabandari, Yayi Suryo (BKM Public Health and Community Medicine, 2021)
Purpose: This study aims to investigate the relationship between physical activity, stress levels, and the incidence of obesity among civil servants (ASN) in Sleman District. Methods: This research used a 1:1 unmatched case-control study design. The research sample consisted of 244 respondents (122 cases and 122 controls) selected by proportional random sampling. Data collection was conducted through interviews using a structured questionnaire, the International Physical Activity Questionnaire (IPAQ), and the Social Readjustment Rating Scale (SRRS). Data analysis was performed using the Chi-Square test and multiple logistic regression. Results: The results showed that 78.3% of respondents were between 35 and 54 years old. Respondents have a final education level of S1/S2 as high as 57.4%. The results of the bivariable analysis showed that moderate physical activity with obesity events (OR = 2.08; 95% CI = 1.05 - 4.05; p-value: 0.027), severe stress levels with the incidence of obesity (OR = 6.81; 95% CI: 0.75 - 59.60; p-value: 0.044) and age 34-54 years with the incidence of obesity (OR = 3.51; 95% CI: 0.92 - 13.37; p-value: 0.049) has a relationship with the incidence of obesity in ASN in Sleman District. The results of the multivariable analysis showed that moderate physical activity had a significant influence on the incidence of obesity in ASN in Sleman District in the final model. Conclusion: Physical activity has a significant association with the incidence of obesity among ASN in the Sleman District. Therefore, it is recommended that the Sleman District Government provide fitness facilities for regular exercise and establish institutional Posbindu (integrated health posts) in each government office (OPD) to serve as routine health checkpoints and consultation centers for ASN.